Learning to think environmentally : while there is still time - Milbrath, Lester W. (State University of New York Press, 1996)
"The survival of planet Earth's nourishing life systems ultimately depends on how we humans think about them. Unfortunately, our culture's assumptions about the way the world works ignore recent scientific understanding of life systems. This book explains the interdependency and delicate balance of biological, geological, and chemical systems as environmental scientists now understand them. It communicates a new way of thinking." "Written in everyday language as a conversation between two neighbors, Learning to Think Environmentally is illustrated with cartoons by Pulitzer Prize-winning cartoonist Tom Toles. It demonstrates that learning the basic principles of environmental thinking is essential to our social, physical, economic, and spiritual well being. This new way of thinking is urgently needed in our public discourse if we are to take a sustainable pathway to the future."--BOOK JACKET.